SISTEM INFORMASI RESERVASI BERBASIS WEBSITE PADA BENGKEL MOBIL BAYU MOTOR PAMULANG - Abdul Azis Marzuqi (2023)
Bayu Motor is a company engaged in the automotive field that serves repair services, which is located in Pamulang District. Vehicle maintenance and repair are important aspects in the mobility of modern society. However, many vehicle owners still face challenges in terms of scheduling, information access and maintenance history management such as at the Bayu Motor Pamulang car repair shop. This final project aims to develop and implement a car repair shop reservation information system that focuses on efficiency and customer experience. The system development used adopts the Waterfall method, PIESCES to detect problems and Blackbox Testing for system testing. The resulting system can make service reservations, order spare parts and make reports. The computerized system design makes it easier for admins to manage reservations and record customer data.